Implementasi Kebijakan Menteri Pertanian Nomor 67 Tahun 2016 Tentang Pembinaan Kelembagaan Petani di Dinas Perkebunan Provinsi Jawa Barat - Mariane, Ine; Herlinda, Herlinda; Sepriadi, Sepriadi (Universitas Bandar Lampung (UBL), 2024)
Farmer institutions as forums for farmer organizations have not yet functioned optimally. This study aims to examine and analyze the implementation of the Minister of Agriculture's Regulation Number 67 of 2016 on Farmer Institutional Development in Indonesia, specifically at the Plantation Service of West Java Province, as well as the factors that support or hinder its success. Using a descriptive qualitative method, the study reveals that communication remains suboptimal due to budget constraints and the large coverage area, while resources are inadequate due to a limited number of human resources (HR). However, the attitude or disposition is favorable, with tasks for regional facilitators or extension workers being clear and continuously implemented. The bureaucratic structure is well-organized, with facilitators providing counseling in accordance with Standard Operating Procedures (SOPs) and maintaining effective communication with farmers. Supporting factors include the quality of human resources, the commitment and support of central and local governments, and the enthusiasm and dedication of targeted farmer groups. On the other hand, challenges include the limited number of HR, the vast agricultural land area, the diverse ages of farmer group members, weak group organizational structures, budget constraints, insufficient facilities and infrastructure for facilitators, poor communication, and the mental attitudes of farmers. Overall, while the policy implementation is generally positive, it remains suboptimal and requires further improvement.